Pengaruh Iklim Organisasi terhadap Efektivitas Pelayanan Pegawai Kantor Camat Kota Utara Kota Gorontalo - Rahmisyari Rahmisyari (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
The Effect of Organizational Climate on the Effectiveness of Employee Services at the North Kota Camat Office, Gorontalo City, The purpose of this study was to determine and analyze the Effect of Organizational Climate on the Effectiveness of Employee Services. This study used a sample of 33 respondents, the questionnaire was used as a primary data collection tool and the data were analyzed using a path analysis tool. Based on the results of this study that the organizational climate consisting of Responsibilities (X1), Awards (X2) and Support (X3), simultaneously had a positive and significant effect on employee service effectiveness (Y) of 0.799 or 79.9% and the remaining 20 , 1% is determined by other factors not examined. The variable of responsibility (X1) partially has a positive and significant effect on the effectiveness of employee services (Y) of 0.451, the variable of appreciation (X2) partially has a positive and significant effect on the effectiveness of employee services (Y) of 0.380 and the variable of support (X3) partial positive and significant effect on the effectiveness of employee services (Y) of 0.323